Application of POC Addition to Nutrients and its Effect on Planting Direction in Lettuce Plants in Vertical Hexagonal Aeroponics - Muhammad Thoriqul Akbar; Hadi Suhardjono; Sutini Sutini (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2025)
Aeroponics is cultivation that can produce lettuce optimally. This research aims to obtain the quality and quantity of lettuce using the vertical hexagonal aeroponics method with the influence of planting direction, sunlight and the addition of liquid organic fertilizer. This research used a factorial Randomized Group Design (RAK) and was repeated three times. The first factor is the Ab mix concentration and the second factor is the planting direction. The lettuce yield variables observed were plant length, number of leaves, harvest yield (root length, wet weight, dry weight) and organoleptic tests. The single factor of adding POC to nutrients influenced the variables wet weight, dry weight and root length, whereas the planting direction treatment only affected root length and the interaction of planting direction treatment and adding POC to nutrients affected organoleptic and stem variables. long. The root length parameters of 58.94 cm, wet weight of 90.59 grams, and dry weight of 8.40 grams are the best parameters if POC is added to nutrition, and treatment of northeastern plantings gives the highest root length, namely 68.73 cm.